A review of gynaecological oncology patients seen in Sir Ganga Ram Hospital Lahore - Randhawa, Sadia Afzal; Humayun, Shamsa (Journal of Fatima Jinnah Medical University, 2020)
Gynaecological cancers represent significant source of morbidity and mortality in women. Female genital malignancies have different geographic distribution which varies from one region to another. Cervical cancer was reported to be the most common malignancy worldwide in 2008.1 However, other literature reviews showed ovarian cancer being more common in different regions of Pakistan.2,3 The objective of this study is to see demographic factors, signs and symptoms, prevalence, and type of tumor in the local patient population presented to a tertiary care hospital in Central Lahore. Patients and Methods: A prospective descriptive study was carried out in Gynaecology Unit 1, Sir Ganga Ram Hospital/Fatima Jinnah Medical University Lahore. All the patients who managed with suspicion or diagnosis of Gynaecological malignancy from August 2012 till August 2017 were included in study. Case notes of all these patients were studied to determine the, age, parity, signs and symptoms and type of tumor. All data was recoded on a predesigned proforma after taking informed consent of the patients and getting approval from hospital ethical committee and was analyzed using SPSS version 20. Results: Total of 100 patients managed for suspected or confirmed gynaecological malignancy during the study period. The most common type of malignancy was ovarian cancer present in 58 (58%) patients. Most common age group for this malignancy was 40-59 years in 24 patients (41%) and 28 (48.27) were having parity of 1 to 5. Common presentation in ovarian cancer was abdominal distension, anorexia and weight loss observed in 21 patients (36.2%). Mucinous cyst adenocarcinoma was the most common histopathology reported in 25 (43%) cases. Next most common type of malignancy was cervical cancer with prevalence of 25%; 13 (52%) were 60 years of age or above. Presenting complaint of per vaginal discharge was present in 9 (36%) out of 25 cases. Histopathology was squamous cell carcinoma in all 25 cases (25%). Uterine carcinoma being third most common malignancy was observed in 17 patients (17%). Most common age group for this cancer was above 60 years in 8 patients (47.08%) with parity of more than 4 in 13 (76.47%). Most common presenting complaint in these patients was postmenopausal bleeding found in 10 cases (58.82%). Uterine adenocarcinoma was the commonest reported histology in 15 (88.73%) of these patients. Conclusion: This study highlights the demographic features, prevalence, signs and symptoms, type of tumor of different types of gynaecological malignancies in the local population. The identification of common modes of presentation may be helpful in early detection and diagnosis resulting in timely intervention which may improve patient outcome